Addressing water and sanitation needs of displaced women in emergencies - Rink de Lange (2013)
Mainstreaming gender in an emergency Water and Sanitation (WatSan) response can be difficult as standard consultation and participation processes take too much time in an emergency. To facilitate a quick response that includes women’s needs, a simple Gender and WatSan Tool has been developed that can also be used by less experienced staff. It is a step-by-step guide on how to collect required data to define design parameters based on ad-hoc consultations with women who will be the users. In 2012 the tool was tested in South Sudan within the context of a regular MSF emergency intervention. Using the tool allowed for a quick and easy way to consult women about the design. Consequently, an increased usage of facilities was observed in the intervention group compared with a control group where the tool was not used.